Chemical composition and tenderness of longissimus dorsi muscle from non- castrated Murrah buffaloes slaughtered at different weights - de Lima Francisco, C. [UNESP]; Mendes Jorge, A. [UNESP]; Bortoleto Athayde, N. [UNESP]; Andrighetto, C. [UNESP]; de Oliveira Roça, R. [UNESP]; de Amorim Ramos, A. [UNESP] (Taylor & Francis, 2007)
Buffalo meat production has been arising interest breeder and emerges as alternative to consumer, more and more demanding of the quality products. Thus, this research was conducted to study the chemical composition and tenderness of Longissimus dorsi muscle from 10 non-castrated Murrah buffaloes slaughtered at different weights. The research was carried in feedlot of School of Veterinary Medicine and Animal Science of the Sao Paulo State University, Botucatu, São Paulo, Brazil. Animals were divided in two groups, received diet ad libitum and slaughtered when reached 450 and 500 kg of live weight. The experiment design was completely randomized, with five repetitions to each treatment. Meat sample from Longissimus dorsi muscle, taken between 12th and 13th ribs, were carried analysis of moisture, crude protein, fat, ash, Longissimus muscle area (LMA), fat thickness (FT), marbling, calorie and tenderness. It did not have significant difference between the groups. Average values at of 76.0; 20.7; 2.1 and 1.2 of moisture, crude protein, fat and ash respectively, were obtained. Calorie, tenderness, LMA, FT and marbling were obtained at average values of 132 kcal/100g; 3.94 kgf; 34.2 cm2; 5.9 mm and 2 points, respectively. Values obtained for tenderness are similar in the literature and has been proving that buffalo meat is tender (< 5kgf). Positive correlation was observed between the protein percentage and the shear force of the meat. The buffalo meat is excellent alternative source of red protein of high biological value to feeding of Brazilian consumers.
Keywords: Buffaloes; Crude protein; Marbling; Shear force